Chile’s Social Outbreak: Not a Student Movement - Bernasconi , Andrés; Leihy, Pete (International Higher Education, 2020)
From October 2019, widespread protests in Chile have aired understandable frustrations and, more perplexingly, vicious violence. There are those who appreciate past compromises in fostering democracy and poverty reduction, and others who see only inequality and stagnation. Baffled academic communities have been unable to foreground consultative proposals for constructive change.